INTUITIVE COGNITION AS A SYNERGISTIC PROCESS (Scientific journal of the Fergana State University, 2024)
This article deals with intuitive knowledge decisions are activated as an organized system in a synergistic state. Intuition is studied as a synergistic process that reflects spiritual phenomenon, spiritual intuition, harmony of spirit and mind, integrity.